Events leading to anterior cruciate ligament injury in World Cup Alpine Skiing: a systematic video analysis of 20 cases - Bere, T.; Flørenes, T. W.; Krosshaug, T.; Nordsletten, L.; Bahr, R. (British Journal of Sports Medicine, 2011)
Background: The authors have recently identified three main mechanisms for anterior cruciate ligament (ACL) injuries among World Cup (WC) alpine skiers, termed as "the slip-catch", "the landing back-weighted" and "the dynamic snowplow". However, for a more complete understanding of how these injuries occur, a description of the events leading to the injury situations is also needed.